2011
DOI: 10.4067/s0718-58392011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Organic Versus Conventional Methods of Fertilization and Weed Control in a Long Term Rotation of Cereals in Semiarid Spain

Abstract: Under semiarid conditions the response of cereal crops to chemical fertilizers and weed control practices with herbicides is often reduced. In fact, the economic profitability of agricultural production in many dryland regions is critically affected by high costs of inputs and low crop yields. As a solution, cropping systems like organic farming, obtaining similar yields and promoting environmental sustainability by reducing fertilizer and herbicides, could be an alternative to conventional systems. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…In this line, Pardo et al . () indicated that the nutrient content increases for legume rotations in semi‐arid conditions, and we found similar results (Table ) (the nutrient contents increased for OF especially in LV and LP). For subsoil horizons (Bt and C), the SOC‐S was higher in all studied soils in OF (Table ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this line, Pardo et al . () indicated that the nutrient content increases for legume rotations in semi‐arid conditions, and we found similar results (Table ) (the nutrient contents increased for OF especially in LV and LP). For subsoil horizons (Bt and C), the SOC‐S was higher in all studied soils in OF (Table ).…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, in soils under no till, crop residues are deposited on the soil surface, with slower decomposition as a result of drier conditions and reduced mineral nutrient availability. In this line, Pardo et al (2011) indicated that the nutrient content increases for legume rotations in semiarid conditions, and we found similar results (Table III) (the nutrient contents increased for OF especially in LV and LP). For subsoil horizons (Bt and C), the SOC-S was higher in all studied soils in OF (Table IV).…”
Section: Soil Organic Carbon and Total Nitrogen Stockssupporting
confidence: 86%
“…Integrated production deploys biological pest control as a useful tool for decreasing the use of pesticides and making production more environmental-friendly, and it is used by over 80% of growers. Today, farmers are increasing their interest in introducing a next step in ecological production, moving toward organic farming, being aware that a reduction in agrochemicals can improve the sustainability of the system (Pardo et al 2011). However, the strict EU organic farming and production regulation in effect since 1991 requires a considerable effort.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in dryland wheat systems have shown little or no response of dryland winter wheat to compost, at least in the short-term (Calderón et al, 2018;Lyon et al, 2012;Pardo et al, 2009;Pardo et al, 2011). While all were conducted in arid and semi-arid dryland wheat systems, these studies represent a range of soil fertility, management history, precipitation levels, and soil type, indicating the importance in teasing out potentially complex interactions between yield response and environmental variables.…”
Section: Discussionmentioning
confidence: 99%